Distribusi Dana Zakat dengan Akad Al-Qard Al-Hasan di PKPU Cabang Yogyakarta dalam Perspektif Mashlahah Mursalah - Faqih El Wafa (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine the application of zakat distribution with the al-qard al-hasan contract of PKPU Yogyakarta branch in the perspective of maqashid sharia. This distribution is in the form of a loan to mustahik which must be returned in full even without interest, according to the information above, zakat funds should be given to mustahik because zakat is the right of mustahik, and one of the conditions for giving zakat is the transfer of property rights to mustahik so that the funds disbursed become rights. mustahik personal. This type of research includes field research (field research). Data was collected by conducting interviews with the parties responsible for the distribution of zakat funds. The distribution of zakat funds carried out by the Yogyakarta branch of PKPU was analyzed using the maslahah mursalah approach. The zakat distribution system at the Yogyakarta branch of PKPU can be narrowed down into 2 forms, namely consumptive (in the form of cash compensation) and productive (business capital lent to the poor in the form of capital money or business tools) including the al-qard al-hasan pattern.